Finite difference methods, theory and applications : 6th International Conference, FDM 2014, Lozenetz, Bulgaria, June 18-23, 2014, Revised selected papers /: 6th International Conference, FDM 2014, Lozenetz, Bulgaria, June 18-23, 2014, Revised selected papers. (2015) - Unknown
No abstract available